Enhancing Students’ Green Ethic-Based Problem Solving Skills in English for Tourism Subject Course - Kanca, I Nyoman; Ginaya, Gede; Sri Astuti, Ni Nyoman; Susyarini, Ni Putu Wiwiek Ary; Astuti, Ni Wayan Wahyu (Politeknik Negeri Bali, 2021)
This study aims to examine the development of students' core competencies in learning English for Tourism at Tourism Department Politeknik Negeri Bali, where the main product is a green ethical-based measurement instrument for Core Competencies Practices of Problem Solving Skills. Two types of instruments have been created and designed and then used to assess the level of Development in the teaching and learning process for students and lecturers. The results of the Students' Report trial show that overall the instrument is suitable for widespread use. Confirmatory factor analysis results also show the validity of the sub constructs for each main construct. The results of the level of development of Core Competencies show that the minimum development of students' Core Competencies is above 4.2. This means that the development of student Core Competencies has been achieved. For this reason, the Core Competencies development model must maintain to be developed, tested and finally implemented.